ISOLATION AND IDENTIFICATION OF DENTAL CARIES BACTERIA AND STUDY OF THEIR SENSITIVITY TO SOME ANTIBIOTICS AND NANOPARTICLES - Noor Tahseen Thanoun Ahmed Al-Amin; Prof.Dr. Yassien Hussein Owaid Al-Jubouri; Assist Prof. Dr. Rana Jalal Shaker (Scholar Express Journals, 2022)
The current study aimed to know the bacterial causes of dental caries, and for this purpose, 850 samples were collected from people with cariesTooth decay for the period from the beginning of November 2020 to the end of March 2021, for both sexes, at different ages ranging from (8-50) years,Then they were collected and transported directly to the laboratory and the samples were planted by plotting on plates of nutritious acar and then acaral blood and mkonkiAnd in solid saline mannitol medium under aerobic conditions , 800 samples gave a positive growth, i.e. 94.11%, which included bacterial speciesStreptococcus mutansBy 357 isolates, or 44.62%, the type Staphylococcus aureus appeared at 248 isolates, or 31%, while Streptococcus pyogenes made up 98 isolates, or 12.25%, while the type Kleebsiella pneumonia appeared in 49 isolates, or 6.12 %, and type Escherichia coli,Appeared by 48 isolates, or only 6%. The sensitivity of the bacteria isolates under study was tested against 3 types of antibioticsClindomycin, Metronidazole, Amoxicillin. Where wasolates of bacteria showed-S. aureusResistance against all antibiotics. For isolates ofStreptococcusIt showed a difference in the response to antibiotics in different racesS. pyogenesshowed a mixed response to antibioticsAmoxicillin, Clindamycin, and Metronidazole showed no effect ,while she wasS. muntansMore responsive to antibioticsAmoxicillin, Clindamycin, Metronidazole,The isolates of bacteria showed-E.coliresistance againstClindamycin, Metronidazole, and the sensitivity of the bacterial isolates under study was tested towards the synergism of the three types of antibiotics used, and the results of the study showed a different response.
Keywords: Metronidazole; Dental Caries; isolates; difference